Nipah virus neurotropism: insights into blood-brain barrier disruption - Al Obaidi, Mazen M Jamil; Muthanna, Abdul Rahman; Mohd Desa, Mohd Nasir (IMR Press, 2024)
The genome of the Nipah virus (NiV) encodes a variety of structural proteins linked to a diverse array of symptoms, including fevers, headaches, somnolence, and respiratory impairment. In instances of heightened severity, it can also invade the central nervous system (CNS), resulting in more pronounced problems. This work investigates the effects of NiV on the blood-brain barrier (BBB), the vital physiological layer responsible for safeguarding the CNS by regulating the passage of chemicals into the brain selectively. To achieve this, the researchers (MMJAO, AM and MNMD) searched a variety of databases for relevant articles on NiV and BBB disruption, looking for evidence of work on inflammation, immune response (cytokines and chemokines), tight junctions (TJs), and basement membranes related to NiV and BBB. Based on these works, it appears that the affinity of NiV for various receptors, including Ephrin-B2 and Ephrin-B3, has seen many NiV infections begin in the respiratory epithelium, resulting in the development of acute respiratory distress syndrome. The virus then gains entry into the circulatory system, offering it the potential to invade brain endothelial cells (ECs). NiV also has the ability to infect the leukocytes and the olfactory pathway, offering it a “Trojan horse” strategy. When NiV causes encephalitis, the CNS generates a strong inflammatory response, which makes the blood vessels more permeable. Chemokines and cytokines all have a substantial influence on BBB disruption, and NiV also has the ability to affect TJs, leading to disturbances in the structural integrity of the BBB. The pathogen’s versatility is also shown by its capacity to impact multiple organ systems, despite particular emphasis on the CNS. It is of the utmost importance to comprehend the mechanisms by which NiV impacts the integrity of the BBB, as such comprehension has the potential to inform treatment approaches for NiV and other developing viral diseases. Nevertheless, the complicated pathophysiology and molecular pathways implicated in this phenomenon have offered several difficult challenges to researchers to date, underscoring the need for sustained scientific investigation and collaboration in the ongoing battle against this powerful virus.